NUMERICAL STUDY OF FREE CONVECTION BOUNDARY LAYER FLOW OF A NANOFLUID PAST AN ISOTHERMAL INCLINED PLATE - AKILU, SULEIMAN (2013)
The steady free convection boundary layer flow of incompressible nanofluid past an isothermal inclined plate is numerically investigated for various physical conditions using Buongiorno model. The governing equations are transformed into a system of coupled and locally similar ordinary differential equations which are solved numerically using animplicit finite-difference method known as the Keller-Box method.